What is the impact of integrated care on the job satisfaction of primary healthcare providers: a systematic review - Mei Liu; Jian Wang; Jiaxu Lou; Ruonan Zhao; Jiahui Deng; Ziyu Liu (BMC, 2023)
Abstract Background and objectives The integration of care influenced the job satisfaction of healthcare professionals, especially affecting primary healthcare providers (PCPs). This study aimed to perform a systematic review to explore the impact of integrated care on the job satisfaction of PCPs on the basis of Herzberg's two-factor theory. Methods This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched 6 electronic databases, including CNKI, WANFANG, PubMed, Web of Science, Cochrane Library, and Embase. Data were retrieved from inception to 19 March 2023. The Mixed Methods Appraisal Tool (MMAT) version 2018 was used to assess the methodological quality of studies for inclusion in the review. Results A total of 805 articles were retrieved from databases, of which 29 were included in this review. 2 categories, 9 themes, and 14 sub-themes were derived from the data. 2 categories were identified as intrinsic and extrinsic factors. Intrinsic factors included 4 themes: responsibilities, promotion opportunities, recognition, and a sense of personal achievements and growth. Extrinsic factors included 5 themes: salaries and benefits, organizational policy and administration, interpersonal relationships, working conditions, and work status. To specify some key information under certain themes, we also identify sub-themes, such as the sub-theme "workload", "work stress", and "burnout" under the theme "work status". Conclusions Findings suggested that the integration of care had both negative and positive effects on the job satisfaction of PCPs and the effects were different depending on the types of integration. Since PCPs played a vital role in the successful integration of care, their job satisfaction was an important issue that should be carefully considered when implementing the integration of care.